Anomalies in the short-range local environment and atomic diffusion in single crystalline equiatomic CrMnFeCoNi high-entropy alloy - Smekhova, Alevtina; Gaertner, Daniel; Kuzmin, Alexei; Buzanich, Ana Guilherme; Schuck, Goetz; Zizak, Ivo; Wilde, Gerhard; Yusenko, Kirill V.; Divinski, Sergiy (Tsinghua University, 2024)
Multi-edge extended X-ray absorption fine structure (EXAFS) spectroscopy combined with reverse Monte Carlo (RMC) simulations was used to probe the details of element-specific local coordinations and component-dependent structure relaxations in single crystalline equiatomic CrMnFeCoNi high-entropy alloy as a function of the annealing temperature. Two representative states, namely a high-temperature state, created by annealing at 1373 K, and a low-temperature state, produced by long-term annealing at 993 K, were compared in detail. Specific features identified in atomic configurations of particular principal components indicate variations in the local environment distortions connected to different degrees of compositional disorder at the chosen representative temperatures. The detected changes provide new atomistic insights and correlate with the existence of kinks previously observed in the Arrhenius dependencies of component diffusion rates in the CrMnFeCoNi high-entropy alloy. © The Author(s) 2024. --//-- This is an open access article Smekhova, A., Gaertner, D., Kuzmin, A. et al. Anomalies in the short-range local environment and atomic diffusion in single crystalline equiatomic CrMnFeCoNi high-entropy alloy. Nano Res. 17, 5336–5348 (2024). https://doi.org/10.1007/s12274-024-6443-6.
The authors thank the Helmholtz–Zentrum Berlin for the provision of access to synchrotron radiation facility and allocation of synchrotron radiation at the BAMline and KMC-3 (CryoEXAFS end-station) beamlines of BESSY II at HZB. Yu. Chumlyakov (Tomsk State University, Russia) is acknowledged for the growth of single crystals. A. S. also acknowledges personal funding from CALIPSOplus project (Grant Agreement No. 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020). A. K. is thankful for the financial support from the Latvian Council of Science project No. lzp-2023/1-0476. S. D. acknowledges financial support by the German Research Foundation (DFG), project DI 1419/24-1. G. W. acknowledges financial support by DFG via SPP2006, project WI 1899/32-2. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the EU Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; diffusion; extended X-ray absorption fine structure (EXAFS); high-entropy alloys; reverse Monte Carlo; short-range order